2021
DOI: 10.1021/acssuschemeng.0c08664
|View full text |Cite
|
Sign up to set email alerts
|

High-Yield Production of Deoxygenated Monomers from Kraft Lignin over ZnO-Co/N-CNTs in Water

Abstract: Catalytic conversion of technical lignin to value-added chemicals and fuels is important for realizing economically viable lignocellulosic biomass refineries. The choice of catalysts and solvents is critical for the effective conversion of the technical lignin to chemicals and fuels by the cleavage of the C−C bonds. In this study, catalytic depolymerization and hydrodeoxygenation of Kraft lignin (KL) were investigated over bimetallic ZnO and Co deposited on N-doped carbon nanotubes (ZnO-Co/N-CNTs) in an aqueou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 84 publications
0
9
0
Order By: Relevance
“…Metal/N-doped carbon materials are widely used in biomass HDO due to strong metal−support interactions, high stability, and excellent surface chemistry (wettability, basicity). 4,29,73,97 N, which is adjacent to C in the periodic table and has a similar atomic size to C, can effectively reduce the structural deformation and form stable N−C bonds of the carbon network, which has been the most introduced exotic element in metal/carbon catalysts due to its unique properties, easy synthesis, abundance, and excellent performance of biomass HDO. 102 Jiang et al 96 synthesized the cobalt loaded N-doped carbon catalyst (Co/NC) for the HDO of vanillin, and nearly quantitative MMP yields were obtained at 10 bar H 2 pressure and 150 °C.…”
Section: Carbon Catalysts For Biomass Hdomentioning
confidence: 99%
See 2 more Smart Citations
“…Metal/N-doped carbon materials are widely used in biomass HDO due to strong metal−support interactions, high stability, and excellent surface chemistry (wettability, basicity). 4,29,73,97 N, which is adjacent to C in the periodic table and has a similar atomic size to C, can effectively reduce the structural deformation and form stable N−C bonds of the carbon network, which has been the most introduced exotic element in metal/carbon catalysts due to its unique properties, easy synthesis, abundance, and excellent performance of biomass HDO. 102 Jiang et al 96 synthesized the cobalt loaded N-doped carbon catalyst (Co/NC) for the HDO of vanillin, and nearly quantitative MMP yields were obtained at 10 bar H 2 pressure and 150 °C.…”
Section: Carbon Catalysts For Biomass Hdomentioning
confidence: 99%
“…Once the preferential adsorption of reactant molecules has occurred, the well-dispersed Pt nanoparticles undergo the next step of C−O bond cleavage. Mushtaq et al 97 investigated catalytic HDO of Kraft lignin (KL) over bimetallic Co-and ZnO-loaded N-doped CNTs (ZnO-Co/N-CNTs) in an aqueous medium, achieving almost 100% conversion of KL at 350 °C and 6 h reaction conditions (Figure 12). The hydrophilicity of N allows better dispersion of the catalyst in aqueous media and promotes catalyst −substrate contact.…”
Section: Carbon Catalysts For Biomass Hdomentioning
confidence: 99%
See 1 more Smart Citation
“…25 Rautiainen et al reported that using formate (or formic acid) as a hydrogen donor and Co-phen/C as a catalyst, birch wood without treatment could be converted into monophenolic compounds in up to 34 wt % yield of total lignin. 26 of bio-oil (52 wt %) and lignin-derived monomers (12.1 wt %) over ZnO−Co/N−CNTs at 350 °C in 6 h. 27 In the previous work, acetophenone was always produced for the hydrogenolysis of β-O-4 ketone, or a mixture of ethylbenzene, acetophenone, and 1-phenylethanol was obtained due to the poor catalyst selectivity. It has been known that the hydrodeoxygenation of aromatic ketones/alcohols is a very important process in chemical synthesis and biomass upgrading.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Rautiainen et al reported that using formate (or formic acid) as a hydrogen donor and Co-phen/C as a catalyst, birch wood without treatment could be converted into monophenolic compounds in up to 34 wt % yield of total lignin . Very recently, Kim et al found that kraft lignin could be converted almost completely with a high yield of bio-oil (52 wt %) and lignin-derived monomers (12.1 wt %) over ZnO–Co/N–CNTs at 350 °C in 6 h …”
Section: Introductionmentioning
confidence: 99%